Making Basic Spices That Are Durable In Add To The Pocket Money Of Unitomo Vocational School Students - Djauhari, Arlin Besari (KARYA ABDI, 2022)
Red chili is a vegetable product that has a spicy taste and is seasonal. Meanwhile, people who like to consume spicy food always need chili as a mixture in cooking. During the chili season the price of red chili is very cheap, and when it is not the chili season the price is very expensive. This situation is an opportunity for Unitomo Vocational High School students to add pocket money at school. Faculty of Agriculture University Dr. Soetomo through the Community Service program provides a solution to this problem. This Community Service Program aims to: 1. Provide counseling to Unitomo Vocational High School students about the process of making basic seasonings made from long-lasting red chilies; 2. Provide business skills training to make basic spices, so that the profits can be used as additional pocket money at school. The implementation method consists of 4 stages, namely a. the observation stage conducts a feasibility study of participants who will be involved in community service; b. counseling stage; and c. the training stage which is the core of the activity in the form of delivery of theory and practice; d. assisting students in carrying out activities starting with the preparation of materials and tools, the process of making basic spices, evaluating product preferences, selling products, to making a profit. The process of making basic seasonings is chili being processed into basic seasoning ingredients consisting of red chilies, shallots and garlic. which has a shelf life of up to 6 months. These basic spices are semi-finished ingredients, meaning that these basic spices can then be used to prepare a number of other dishes, including shrimp fried rice, fried tempeh/dried tofu sauce, egg bali, eggplant balado, lodeh bamboo shoots, and others. The way to make the basic seasoning is 1 kg of red chilies, 400 g of shallots and 400 g of garlic. All ingredients are crushed and then sautéed with a little oil until coarse, then dried, then floured until it becomes powder and then packaged in airtight plastic, and stored in a dry place. This dried basic seasoning is ready to be used at any time, even when it's not chili season where the price of chili is very expensive, we can still taste spicy food. In addition, the profits from the basic seasoning business can be used to increase pocket money or school needs